Iron supplementation reduces the frequency and severity of breath-holding attacks in non-anaemic children - Anthony Zehetner (Clinics and Practice, 2011)
Iron supplementation reduces the frequency and severity of breath-holding attacks (BHAs), particularly in children with iron deficiency. The issue of iron supplementation is less clear for Westernized children with BHAs who present to an outpatient community clinic and are not iron-deficient. This is the first reported case series of iron-replete children with frequent and disabling breath-holding attacks who have responded to a course of oral iron supplementation. This intervention is safe, improves quality of life for both child and carer, and is significantly cost-effective in terms of health resource utilization.